Autoregulation of the glial gene reversed polarity in Drosophila - Jamie L. Wood; Saroj Nepal; Bradley W. Jones (Scientific Reports)
Abstract During development, cells of the nervous system begin as unspecified precursors and proceed along one of two developmental paths to become either neurons or glia. Work in the fruit fly Drosophila melanogaster has established the role of the transcription factor Glial cells missing (Gcm) in directing neuronal precursor cells to assume a glial cell fate. Gcm acts on many target genes, one of which is reversed polarity (repo). repo encodes a homeodomain transcription factor and is necessary for the terminal differentiation of glial cells. Transient Gcm expression is followed by maintained expression of repo. Evidence supports autoregulation to be one of the mechanisms that maintains repo expression, as ectopic repo expression in embryos can activate repo-lacZ reporter constructs. In this paper we further explore the ability of repo to activate reporter constructs in transgenic embryos and in cultured S2 cells. We provide further evidence that Repo protein acts as a transcription factor on its own regulatory DNA sequence. We report that three canonical Repo binding sites (RBSs) are located within the upstream 4.3 kilobase repo cis-regulatory DNA (CRD). The upstream 2 kb within the repo CRD has remarkable repo-dependent gene expression activity, and mutagenesis of RBS1 in this 2 kb region results in a significant decrease in repo-induced reporter gene expression in both systems. Our results in cell culture experiments also show that RBS2 and/or RBS3 can affect repo-dependent gene expression in the context of the whole upstream repo CRD. Mutagenesis of both RBS2 and RBS3 in the repo CRD, leaving RBS1 intact, significantly reduces repo-induced reporter gene expression. These results suggest that all three canonical RBSs may be cooperatively involved in autoregulation of repo expression.